2017
DOI: 10.1002/cmdc.201700026
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Topoisomerase Inhibitor of Intense Pro‐Apoptotic and Antileukemic Nature for Cancer Treatment

Abstract: Classic cytotoxic drugs remain indispensable instruments in antitumor therapy due to their effectiveness and a more prevalent insensitivity toward tumor resistance mechanisms. Herein we describe the favorable properties of 6-(N,N-dimethyl-2-aminoethoxy)-11-(3,4,5-trimethoxyphenyl)pyrido[3,4-c][1,9]phenanthroline (P8-D6), a powerful inducer of apoptosis caused by an equipotent inhibition of human topoisomerase I and II activities. A broad-spectrum effect against human tumor cell lines at nanomolar concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 56 publications
0
23
0
1
Order By: Relevance
“…Previously, we documented the dual inhibitory potential of P8-D6 against Topo I and II under cell-free conditions, as well as its strong cytotoxic effects on multiple cell lines [5]. However, the mechanism of action was not fully elucidated, leaving open research questions to be addressed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we documented the dual inhibitory potential of P8-D6 against Topo I and II under cell-free conditions, as well as its strong cytotoxic effects on multiple cell lines [5]. However, the mechanism of action was not fully elucidated, leaving open research questions to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo toxicity study on athymic nude mice indicated reversible toxic effects at a concentration of 5 mg P8-D6 kg −1 body weight [5]. Adverse hepatotoxic effects are currently being investigated in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations